Investigation of surface free energy of the glassceramic coatings on titanium for medical purposes - Savvova, Oksana; Shadrina, Galina; Babich, Olena; Fesenko, Оleksiy (Lviv Polytechnic National University, 2015)
Biocompatible calcium silicophosphate glassceramic coatings for titanium on the base of glasses in R₂О–RO–RO₂–R₂O₃–P2O₅–SiO₂ system have been obtained. The influence of crystallization ability and roughness of experimental coatings on their surface free energy has been established. The use of titanium implants with applied apatite-containing glass-ceramic coating will significantly increase biocompatibility of the prosthetic implant and will reduce the time of its union with the bone.

Одержано біосумісні кальційсилікофосфатні склокристалічні покриття по титану на основі стекол системи R₂О–RO–RO₂–R₂O₃–P2O₅–SiO₂. Встановлено вплив кристалізаційної здатності та шорсткості отриманих покриттів на вільну енергію їх поверхнi. Встановлено, що використання титанових імплантатів з нанесеним на нього апатитвмісним склокристалічним покриттям суттєво підвищує біосумісність ендопротезу та дає можливість скоротити термін зрощування його з кісткою.
Дослідження вільної енергії поверхні склокристалічних покриттів по титану медичного призначення
Keywords: glass-ceramic coating; titanium; roughness; surface free energy; покриття склокристалічні; титан; шорсткість; вільна енергія поверхні